Metabolomics-Based Profiling of Clerodendrum speciosum (Lamiaceae) Leaves Using LC/ESI/MS-MS and In Vivo Evaluation of Its Antioxidant Activity Using Caenorhabditis elegans Model - Fadia S. Youssef; Mansour Sobeh; Malak Dmirieh; Hanin A. Bogari; Abdulrahman E. Koshak; Michael Wink; Mohamed L. Ashour; Sameh S. Elhady (MDPI AG, 2022)
We investigated the antioxidant activity of the total methanol extract of C. speciosum leaves (CST), the ethyl acetate (CSE), and the remaining aqueous (CSR) fractions in vitro, in vivo using Caenorhabditis elegans model, and in silico. LC-ESI-MS/MS analysis was employed for metabolic profiling of CST. ADME/TOPAKT prediction was performed to determine the potential pharmacokinetic, pharmacodynamic, and toxicity properties of the major identified phytoconstituents. All examined samples showed considerable antioxidant activity where CST, CSE, and CSR displayed EC50 values of 27.1, 16.2, and 21.3 µg/mL, respectively, in 2,2-diphenyl-1-picrylhydrazyl (DPPH•) assay, whereas they showed 11.44, 16.27, and 12.16 Fe2+ equivalents/mg of sample, respectively, in ferric reducing antioxidant power (FRAP) assay. CST, CSE, and CSR displayed total phenolic content of 262, 326, and 289 mg GAE/g sample, respectively. In vivo antioxidant study revealed that CST at 150 μg/mL increased the survival rate of C. elegans by 71.88% compared to untreated group. Regarding intracellular reactive oxygen species (ROS), worms treated with 150 μg/mL of CSE exhibited 60.42% reduction of ROS compared to the untreated group. Quantitation of hsp-16.2/GFP expression in Caenorhabditis elegans showed that worms treated with 150 μg/mL of CSR exerted 40.43% reduction in fluorescence with respect to the untreated group. LC-ESI-MS/MS of CST revealed the presence of sixteen secondary metabolites belonging mainly to polyphenolics with phenyl propanoids constituting the major detected class. The in silico study showed that rosmarinic acid displayed the best fitting within the active sites of Daf-2 protein with considerable safety profile and limited pharmacokinetic and pharmacodynamic that could be slightly enhanced by certain treatment.